Statistical Analysis and Optimization for VLSI: Timing and Power - Srivastava, Ashish; Sylvester, Dennis; Blaauw, David (Integrated Circuits and Systems, 2005)
Statistical Analysis and Optimization for VLSI: Timing and Power is the first book summarizing the state-of-the-art in the newly emerging field of statistical computer-aided design (CAD) tools. The very latest research in statistical timing and power analysis techniques is included, along with efforts to incorporate parametric yield as the key objective function during the design process. The emphasis is on algorithms, modeling approaches for process variability, and statistical techniques that are the cornerstone of the probabilistic CAD movement. Statistical Analysis and Optimization for VLSI: Timing and Power will allow new researchers in this area to come up to speed quickly, as well as provide a handy reference for those already working in CAD tool development.